2015
DOI: 10.1039/c4ra16490c
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid polypeptide hydrogels produced via native chemical ligation

Abstract: The NCL crosslinked hybrid hydrogels composed of poly(γ-glutamic acid) and ε-poly-lysine have good biocompatibility and tunable properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…When the amount of silver(I) salt was reduced the yield decreased significantly indicating that stoichiometric amount of additive must be used (entry 9). Further optimization using different silver(I) additives showed that silver(I) salts generally promote the thiolactone aminolysis except for AgCl due to poor solubility in organic solvents (entry [10][11][12][13][14]. Some counterion effect was observed and the highest product yield of 92% was achieved with AgOTf.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the amount of silver(I) salt was reduced the yield decreased significantly indicating that stoichiometric amount of additive must be used (entry 9). Further optimization using different silver(I) additives showed that silver(I) salts generally promote the thiolactone aminolysis except for AgCl due to poor solubility in organic solvents (entry [10][11][12][13][14]. Some counterion effect was observed and the highest product yield of 92% was achieved with AgOTf.…”
Section: Resultsmentioning
confidence: 99%
“…[11] As protein homocysteinylation has been associated to be a risk factor of vascular diseases such as atherosclerosis, [12] related biomedical studies have been done. [13] In recent years, γ-thiolactone, has been exploited in the preparation of hydrogels via Native Chemical Ligation (NCL), [14] protein modifications, [15] and the synthesis of polymers by aminolysis with simple amines. [16] β-thiolactones have been quite thoroughly studied for various peptide bond formation and for applications in chemical biology.…”
Section: Introductionmentioning
confidence: 99%
“…Pioneering work, 15 elegantly illustrated by Crich and co-workers, has demonstrated the connections of single amino acids in the presence of exogenous thiol activators, however the investigation of β-thiolactones in the context of polypeptides as well as at sterically hindered sites has been elusive. 16 Our approach commenced with the cyclization of commercially available Boc- l -cysteine and Boc- l -penicillamine (Boc-Cys and Boc-Pen respectively) 15 , 17 to furnish thiolactones 2 and 3 (ref. 18 ) in high yield ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…This behavior allows for incorporation of drugs and cells in viscous solution at low temperature and gelation at elevated temperature. Synthetic polypeptides combining the advantages of synthetic polymers and biological performances of peptides are promising candidates for thermal‐responsive hydrogels . The secondary conformation provides complementary structural stability and the diversity of amino acid residues offers highly tunable functionality to the hydrogel .…”
Section: Background and Originality Contentmentioning
confidence: 99%